Experience in using high-frequency georadar for landscape snow survey in the vicinity of Kirovsk (the Khibiny Mountains) and Apatitу (the Kola Peninsula) - R. A. Chernov; A. Ya. Muraviev (Лëд и снег)
The results of processing of a profile snow-measuring survey of snow cover in the Khibiny Mountains are presented. The survey was performed during the period of maximum snow accumulation (March of 2020) on the main elements of the landscape: mixed forest on the plain, open woodlands at the bottom of valleys, plateaus, wooded slopes, and upper slopes without woody vegetation. The averaged values of snow storage for different types of the landscapes were obtained for the period of the maximum snow accumulation in the snowy winter of 2019/20. The maximum snow storage (> 700 mm w.e.) was determined for areas on the high plateaus and open woodlands at the bottom of valleys. Minimum snow storage (> 400 mm w.e.) was recorded in areas of mixed forest on the plain and on an ice cover of lakes. Measurements of snow depth were carried out by the standard method (a handspike) and the ground-based radio-echo sounding using georadar with the frequency of 1600 MHz. The accuracy of this method allows measuring of the snow depth with accuracy of 1 cm for a dense snow and 2 cm for a loose one. Thus, the accuracy of measuring the snow depth with the radar is comparable to the accuracy of a handspike. A large number of radar measurements of snow depth on the profiles makes possible to determine the spatial variability of this value and its statistical characteristics. As a result, a vertical gradient of snow accumulation was defined as 25 mm w.e. per 100 m. The smallest spatial variability of snow depth was observed on profiles in the forests on the plain, in woodlands, and on the upper slopes. On profiles with complex relief (plateau, lower slopes), the spatial variability of snow depth is significant – the standard deviation was within limits of 30%. Based on the results of processing the field data, a map of snow storage over the studying area during the period of maximum snow accumulation was constructed. When constructing the map, we took into account the averaged data of the measurements for each type of landscape, the boundaries of woody vegetation, the height, steepness of slopes, and the high-altitude gradient of snow accumulation. It was found that features of the spatial distribution of snow cover were primarily due to the location of natural landscape complexes. The role of changes in snow storages with altitude was found to be insignificant.